Preservation, extraction and analytical methods for faecal progesterone metabolite in cows and immune response to pregnanolone hemisuccinate in rabbits - Peter, Innocent Damudu (2019)
Monitoring reproductive function using faecal progesterone metabolite evaluations is a well-established technique in gazelles, horses, baboon, pigs, rhinoceros, elephants and should be extensively applied in domestic animals. Some factors however, prevent the application of this non-invasive technique to monitor reproduction in animals. These factors include paucity of practical information on stability of faecal progesterone metabolites under different preservation and extraction methods as well as sensitivity and specificity of analytical techniques. Therefore, general objective of this study was to evaluate preservation, extraction and analytical techniques for progesterone metabolite in faeces of cows; determine plasma progesterone and progesterone metabolite profiles in pregnant and non-pregnant cows; modify existing high performance liquid chromatography (HPLC) method for steroid hormones for the simultaneous detection of multiple progesterone metabolites in faeces of cows and to determine the immune responses and cellular changes following administration of low dose of pregnanolone hemisuccinate in rabbits. Progesterone metabolites were extracted from faecal samples using already established procedures and their concentrations together with plasma progesterone levels were determined using radioimmunoassay. A mobile phase made of distilled water and acetonitrile (70:30 v/v) and a stationary phase made up of C18 column coupled to an Agilent HPLC 1100 series module was modified from existing HPLC method of steroid hormones to detect progesterone metabolites in faeces of cows. This modified HPLC method was hypothesized to be able to serve as an alternative to use of immunoassay on the analysis of progesterone metabolite in animals. Male rabbits were parenterally administered with pregnanolone hemisuccinate on day 0 and were given a booster dose on day 14 so as to produce group specific antibody to progesterone metabolites. Antibody response was determined using IgG and IgM evaluations using ELISA. The results show that there is no statistically significant difference in progesterone metabolite concentration in faeces that were dried at 70°C (9.33±5.05 ng/g), 50°C (5.66±4.19 ng /g) or at 90°C (5.29±2.51 ng/g). Similarly, radioimmunoassay technique was used to determine the stability of progesterone metabolites in oven dried and fresh faecal samples. Faecal progesterone metabolite concentrations were found to be higher when extracted from oven-dried samples (2.06±1.58 ng /g) as compared to extraction from fresh faecal samples (0.49±0.30 ng /g). This difference was found to be statistically significantly (P<0.05). When un-preserved faeces were left exposed to environmental conditions for several days, progesterone metabolite concentrations therein were observed to rise from 11.04±7.68 ng/g at 0 hrs to maximum value of 31.71±10.33 ng /g at 48 hrs and thereafter decline to 36.62±12.30 ng/g after 216 hrs. There was no statistically significant difference (P>0.05) among these values. The relationship between faecal progesterone metabolites concentration and plasma progesterone concentration in cows were also investigated in this study. The results showed a correlation between plasma progesterone and faecal progesterone metabolites in pregnant (r=0.211, n=8, p=0.23) and in non-pregnant cows (r=0.209, n=8, p=0.35). A High-Performance Liquid Chromatography (HPLC) method for steroid hormones commonly employed in other species of animals was modified and used in this study for cows using 5β-pregnan-3α-ol-20-one and 3β-Hydroxy-5α- pregnan-20-one sulphate pyridine salt as internal standards. UV detection was employed to monitor the eluent from a stationary phase at an excitation wavelength of 254 nm and an emission wavelength of 360 nm. The linearity of the calibration curve was obtained in the concentration range of 500-7500 µg/µL for 5β-pregnan-3α-ol-20- one and 3-15 µg/µL for 3β-Hydroxy-5α-pregnan-20-one sulphate pyridine salt respectively. The co-efficient of determination was found to be 0.9977 for 5β-pregnan- 3α-ol-20-one and 0.9776 for 3β-Hydroxy-5α-pregnan-20-one sulphate pyridine salt. The production of group specific antibodies for progesterone metabolites using the immunogen in rabbits was not achieved in this study. This could have been due to minute amount of the immunogen used or a defective bioconjugation method or due to inherent molecular properties of 5β-pregnan-3α-ol-20-one. Histopathological, haematological and biochemical parameters did not significantly differ between control and immunised rabbits in this study. This study provides practical and reliable information on faecal progesterone metabolite levels exposed to different storage, preservation and extraction parameters in cows. Best results for the analysis of faecal progesterone metabolites in cows are obtained when faeces are dried at 70°C and are extracted soon after voiding. The correlation observed between faecal progesterone metabolites and plasma progesterone concentrations shows that faecal progesterone metabolites concentration can be used for determination of reproductive status in cows. The HPLC method described in this study is simple, practical and rapid and can be applied for determination of progesterone metabolite concentration. It is therefore recommended that the information provided by this study be utilised in the non- invasive study of reproductive function in cows. These techniques are simple, reliable and can be performed within a short time. Group specific antibodies were not produced using 5β-pregnan-3α-ol-20-one-hemisuccinate, it is recommended that a modification in the bioconjugation method used or immunisation procedure be performed. Furthermore, other progesterone metabolites could be used to produce group specific antibodies and thereafter used in immunoassays to produce a more specific and sensitive analysis.